Piętno technologii – nomofobia i FoMO jako przykłady lęków współczesnej młodzieży - Czerski, Wojciech Marcin (Kultura-Społeczeństwo-Edukacja, 2022)
There is no doubt that new technologies are the hallmark of modern times. For young people, the digital world is a natural environment for their functioning in everyday life. Smartphones and social media accompany them almost everywhere. Many of them, following their idols, not only like and comment on what others do, but also create their own image online. This often leads them to lose themselves in what they are doing, and when, for some reason, there is no access to a device or SNS, it results in their anxiety and stress. The ongoing pandemic has, in a way, “forced” many of us to have more contact with new technologies. Sitting in front of a computer/smartphone for hours, while studying/working remotely is not without its consequences on physical as well as mental health. There are two increasingly common fears, among the results of the excessive use of smartphones and e.g. social media (mainly used by young people), related to the use of new technologies: nomophobia and FoMO. The former is a kind of separation anxiety related to not having access to a mobile phone. The second one is characterised by people who use social media without restraint, when they cannot check what is happening on their favourite platforms. The aim of this article is to present the characteristics of both phenomena, the means of diagnosis and the results of national and international research showing their scale.